Natto extract inhibits infection caused by the Aujeszky's disease virus in mice - Kobayashi, Junya; Wen, Rongduo; Nishikawa, Takanobu; Nunomura, Yuka; Suzuki, Takehito; Sejima, Yudai; Gokan, Toshiya; Furukawa, Makio; Yokota, Tomoko; Osawa, Nanako; Sato, Yoko; Nibu, Yutaka; et al. (Microbiology and immunology, 2023)
Aujeszky's disease virus (ADV), also known as Suid alphaherpesvirus 1, which mainly infects swine, causes life-threatening neurological disorders. This disease is a serious global risk factor for economic losses in the swine industry. The development of new anti-ADV drugs is highly anticipated and required. Natto, a traditional Japanese fermented food made from soybeans, is a well-known health food. In our previous study, we confirmed that natto has the potential to inhibit viral infections by severe acute respiratory syndrome coronavirus 2 and bovine alphaherpesvirus 1 through their putative serine protease(s). In this study, we found that an agent(s) in natto functionally impaired ADV infection in cell culture assays. In addition, ADV treated with natto extract lost viral infectivity in the mice. We conducted an HPLC gel-filtration analysis of natto extract and molecular weight markers and confirmed that Fraction No. 10 had ADV-inactivating ability. Furthermore, the antiviral activity of Fraction No. 10 was inhibited by the serine protease inhibitor 4-(2-Aminoethyl) benzene sulfonyl fluoride hydrochloride (AEBSF). These results also suggest that Fraction No. 10, adjacent to the 12.5 kDa peak of the marker in natto extract, may inactivate ADV by proteolysis. Our findings provide new avenues of research for the prevention of Aujeszky's disease.